Experiential Avoidance and Post-traumatic Stress Symptoms Among Child Abuse Counselors and Service Workers: A Brief Report - Miller, Michelle L. (Journal of interpersonal violence, 2022)
Professionals who counsel and serve survivors of childhood abuse may be at risk of experiencing symptoms of post-traumatic stress disorder (PTSD), which can be exacerbated by cognitive and emotional processes. It is hypothesized that (1) a significant proportion of professionals who primarily serve child abuse survivors experience elevated levels of PTSD symptoms and (2) elevated PTSD symptoms are associated with psychological inflexibility processes, specifically increased experiential avoidance, cognitive fusion, and emotion regulation difficulties. Child abuse counselors and service workers (N = 31) in a major metropolitan area were recruited for a small pilot study. Participants completed self-report measures of PTSD symptoms and levels of psychological flexibility processes. A significant proportion of counselors endorsed clinically significant PTSD symptoms (n = 13, 41.9%). PTSD symptoms were significantly associated with experiential avoidance (r = .54, p < .01) and emotion regulation difficulties (r = .51, p < .01). These associations remained significant after controlling for the personality trait of emotional stability/neuroticism. These findings suggest that PTSD symptoms may be common among child abuse counselors and service workers, and these symptoms tend to be of greater intensity when responded to in avoidant and inflexible ways.